The ambiguity of loss affects some, but not all autobiographical memories: redemption and contamination, agency and communion. Issue 10 (26th November 2019) - Huang, Manxia; Habermas, Tilmann
ABSTRACT: Compared with clear-cut loss by death, ambiguous loss is defined as a loss that is not definite because the person is missing or mentally absent but physically present (e.g., through Alzheimer's disease). We expected the ambiguity of loss to show in psychologically more compromised loss memories and self-defining memories, but not in autobiographical memories in general. Thirty Chinese adults who had lost a parent through death, thirty whose parent had gone missing, and thirty who cared for a demented parent narrated their loss experiences and memories of sad and turning-point events as well as self-defining memories. Individuals with ambiguous loss narrated the loss and a self-defining memory with more contamination and fewer redemption sequences, and only the loss memory with fewer themes of agency and communion than individuals with definite loss, but not in memories of sad and turning point events. Effects of ambiguity of loss were independent of prolonged grief, which in turn independently predicted some of these effects. Thus the ambiguous quality of loss predicts effects on loss memories and self-defining memories independently of psychiatric symptoms.